1211 The stress check program: an evaluation of the first-year implementation of the new national workplace mental health program in japan. (24th April 2018) - Kawakami, N; Imamura, K; Asai, Y; Watanabe, K; Tsutsumi, A; Shimazu, A; Inoue, A; Hiro, H; Odagiri, Y; Yoshikawa, T; Yoshikawa, E
Abstract : Introduction: The Stress Check Program mandates workplaces with 50 or more employees in Japan to provide their employees with an opportunity for a stress survey (the stress check), followed by a doctor interview for employees with high stress. Improvement of psychosocial work environment based on analysis of the stress check data is also recommended. The program went into its first year round between December 2015 and November 2016. The current paper overviews the implementation and effectiveness of the program in the first year. Methods: We reviewed reports from prefectural (local) labour bureaus wherever available. A prospective study of workplaces (n=217) randomly selected was conducted to know the implementation and related costs. A prospective study of an internet sample of full-time workers (n=2500) was also conducted to know the effects of the program for improving psychological distress. A workshop was held to listen to occupational health professionals and human resource personnel who engaged in running the program at their workplaces. Result: Prefectural labour bureaus reported that about 80% of workplaces implemented the program; the participation rate to the stress check was high (74% to 94%); only a small proportion of employees with high stress took the doctor interview. A similar pattern was found in the workplace cohort. In the cohort of workers, psychological distress was improved in a group that participated in the stress check and experienced work environment improvement significantly better than in a control group who did neither. Occupational health professionals had some difficulties in implementing the new program in the first year, while they planned to improve their practice in the second year. Discussion: The Stress Check Program was well implemented in the first year, while the beneficial effect of the program may be limited to those who experienced work environment improvement following the stress check.